Higher likelihood of success in pregnancy in patients with high serum basal anti-müllerian hormone concentrations: An age-stratified analysis of 4516 women undergoing in vitro fertilization. Issue 5 (2016) - Ye, Hong; Zhang, Xiaodong; Huang, Guoning
No abstract available